Serum and renal tissue markers of nephropathy in rats under immunosuppressive therapy: cyclosporine vs sirolimus - Sereno, J. (2015)
Cyclosporin (CsA) has been progressively replaced by other drugs with putatively fever side effects, including nephrotoxicity and hypertension. Sirolimus (SRL) is one of the main options for management of kidney transplant patients in the post-CsA era. It shows identical efficacy with apparently less cardiorenal side effects than CsA. However, doubts remain concerning the mechanisms of putative renoprotection by SRL as well as the best serum and/or tissue markers for nephropathy, as assessed in this study employing CsA- and SRL-treated rats. Three groups (n = 6) were treated orally during a 6-week protocol: control (vehicle); CsA (5 mg/kg body weight per day Sandimmun Neoral); SRL (1 mg/kg body weight per day Rapamune). Blood pressure and heart rate were assessed with a "tail cuff". Renal dysfunction and morphology were characterized using serum creatinine and blood urea nitrogen (BUN) levels as well as hematoxylin and eosin and periodic acid Schiff staining, respectively. We examined serum concentrations of interleukin (IL)-2, IL-1β, high-sensitivity C-reactive protein, tumor necrosis factor TNF-α, and vascular endothelial growth factor and kidney mRNA expression of interleukin-1β (IL-1β), tumor protein 53 (TP53), mammalian target of rapamycin (mTOR) and proliferating cell nuclear antigen (PCNA), as well as markers of lipid peroxidation in the kidney and serum. Both CsA and SRL induced significant increases in systolic and diastolic blood pressure, but only CsA caused tachycardia. CsA-treated rats also displayed increased serum creatinine and BUN levels, accompanied by mild renal lesions, which were almost absent among SRL-treated rats, which presented hyperlipidemic and hyperglycemic profiles. CsA-induced nephrotoxicity was accompanied by kidney overexpression of inflammatory and proliferative mRNA markers (IL-1β, mTOR and PCNA), which were absent among SRL group. In conclusion, the antiproliferative and antifibrotic character of SRL may explain its less nephrotoxic profile. Renal over expression of mTOR in the CsA-treated group, associated with renal dysfunction and structural damage, reinforces the potential beneft of SRL as a strategy to reduce CsA-evoked nephrotoxicity.